Application of brain-computer interface system in communication of people with severe motor deficits - Jovanović-Simić, Nadica; Arsenić, Ivana; Daničić, Zorica (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Maintaining and improving communication skills of people with severe motor deficits are the main goals of speech therapy. Brain-computer interface systems can be used as a means of communication in this group of users, since they allow them to control external devices with the help of brain activity. This assistive technology represents a new communication channel between the human brain and computers, or other devices. These systems translate the user’s intention, reflected in brain signals, into the output used to control an external device, without muscular activity. Objective. The aim of this paper was to describe and list basic types and divisions of the brain-computer interface system, as well as their development for communication in people with severe motor deficits. Methods. A systematic review of the available literature was performed by searching electronic databases available through the service of the Serbian Library Consortium for Coordinated Acquisition – KOBSON, as well as through Google Scholar and Research Gate. Conclusion. Early communication systems, based on the interpretation of brain waves, provided answers to simple ”yes/no” questions. After that, they were also used in spelling methods, whose speed became higher over time. The development of a brain-computer interface system aims to reduce the length of training, as time-consuming training is one of the main obstacles for the users. In addition, research in this area is aimed at improving performance in all parts of the communication system, as well as developing a reliable interface between users and computers.